2013
DOI: 10.1007/s11434-013-5863-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of static coarsening of two-phase titanium alloy in the α+β two-phase region at different temperature by a cellular automata method

Abstract: A cellular automata (CA) method was employed to model static coarsening controlled by diffusion along grain boundaries at 1173 K and through the bulk at 1213 and 1243 K for a two-phase titanium alloy. In the CA model, the coarsening rate was inversely proportional to the 3rd power of the average grain radius for coarsening controlled by diffusion along grain boundaries, and inversely proportional to the 2nd power of the average grain radius for coarsening controlled by diffusion through the bulk. The CA model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In this case, the characteristic lengths of the diffusion pathways are much larger than the size of the grains . According to the experimental studies and numerical simulations, the obtained value n ≈ 4 corresponds to the grain growth in (αTi) and (βTi), which is controlled by diffusion along grain and/or interphase boundaries. Note that similar result was obtained theoretically in ref .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In this case, the characteristic lengths of the diffusion pathways are much larger than the size of the grains . According to the experimental studies and numerical simulations, the obtained value n ≈ 4 corresponds to the grain growth in (αTi) and (βTi), which is controlled by diffusion along grain and/or interphase boundaries. Note that similar result was obtained theoretically in ref .…”
Section: Discussionmentioning
confidence: 84%
“…These images also indicate the simultaneous growth of (αTi) and (βTi) grains. Numerical modeling of the growth of grains in two‐phase polycrystal shows that the growth law with n = 3 corresponds to a process of coarsening of grains, controlled by the bulk diffusion . The authors of ref .…”
Section: Discussionmentioning
confidence: 99%
“…Cellular automaton (CA) has provided the capability to simulate and predict the evolution of microstructure during metal forming processes [23][24][25][26]. In particular, CA methods have been developed to simulate the microstructure evolution governed by DRX during hot forming processes of various metals such as steels [23,[27][28][29][30][31][32][33], copper [24,25,[34][35][36][37], magnesium alloys [26,38,39], and titanium alloy [40,41]. These previous works demonstrated that the CA method is a computation-efficient numerical approach to simulate microstructure evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Since Hesselbarth [123] et al used the cellular automaton approach for the simulation of recrystallization, in the past several decades, it gradually becomes very promising and popular for simulating the microstructure evolution due to its computation efficiency, flexibility in multi-scale bridging, and physical consistency. Cellular automaton method has been successfully performed in two-or three-dimensional modeling and simulations of dynamic and static recrystallization [124,125], grain coarsening [126], solidification [126], solid-state phase transformation [127], micro-shear band and shear band propagation [128], cracks propagation [129], etc. It provides a deeper insight into the mechanism and morphological complexity of them without timeconsuming solution of complicated partial differential equations.…”
Section: Cellular Automaton Modelsmentioning
confidence: 99%